How Does AI Enable Independent Living for Seniors? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2017)
The global population is aging at an unprecedented rate, bringing both opportunities and challenges. One of the most significant challenges is ensuring that ...
Keywords: AI in Geriatrics; Enable; Independent; Living; Artificial Intelligence; Machine Learning; Healthcare